Multifunctional Spirocyclic Systems. (7th December 2009) - Lukyanov, Boris; Vasilyuk, Gennadii; Mukhanov, Eugene; Ageev, Leonid; Lukyanova, Maria; Alexeenko, Yury; Besugliy, Serguei; Tkachev, Valeri
Abstract : New spiropyrans with different substituents in the benzopyran fragment have been synthesized and investigated. It was shown that introduction of aldehyde group in the structure of spiropyrans gives a possibility to obtain new functionalized compounds. Effects of the substituents on the photochromic behavior were studied.